Penerapan Metode Ceramah dan Partisipasi Belajar Siswa dalam Pembelajaran Bahasa Indonesia di MA Bahrul Ulum - Nuril Isabillah; Valentina Eka Amelia; Hemas Haryas Harja Susetya (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the implementation of conventional teaching strategies (lecture method) and students’ learning participation in Indonesian language learning at MA Bahrul Ulum. This study employed a descriptive qualitative approach with a phenomenological design. The research subjects consisted of two Indonesian language teachers and 42 students selected through purposive sampling. Data were collected through observation, interviews, and documentation, and were analyzed using the interactive analysis model of Miles and Huberman. The findings revealed that students’ learning participation was dominated by listening and note-taking activities, while questioning, answering questions, and summarizing activities remained limited. Analysis based on the student engagement theory and the ICAP Framework indicated that students’ engagement was still at the levels of passive engagement and active engagement and had not yet reached constructive engagement. The use of the ICAP Framework in this study was intended to provide a more detailed description of the quality of students’ engagement during the learning process. This study contributes by mapping students’ learning participation in Indonesian language learning based on the level of engagement demonstrated by students. The study concludes that the lecture method is capable of facilitating the delivery of learning materials; however, it has not been optimal in encouraging verbal participation and deeper cognitive engagement among students. The findings may serve as a reference for Indonesian language teachers in designing learning activities that promote greater student engagement throughout the learning process.